Assesing the Effects of Self-Efficacy and Task Complexity on Internal Contral Audit Judgement - Takiah Mohd Iskandar; Zuraidah Mohd Sanusi (Asian Academy of Management Journal of Accounting and Finance, 2011)
This study examines the effects of self-efficacy and task complexity on audit judgment performance. Self-efficacy refers to the belief that a person has the capacity to organise and execute the course of action required to produce the desired outcome. The study employs a field experiment involving auditors from small and medium audit firms to evaluate internal control audit tasks. Using hierarchical regression analysis, the results indicate that auditors with high self-efficacy perform better audit judgments than those with low self-efficacy. The results also show the negative effects of task complexity on audit judgment performance. High self-efficacy contributes to better audit judgment performance when the tasks are simple. For complex tasks, however, high self-efficacy does not contribute to better audit judgment performance. This paper enhances the theoretical development of the concepts of audit judgment and decision-making by recognising the role of self-efficacy within the framework of social cognitive theory.